2021
DOI: 10.21203/rs.3.rs-533347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics And Outcomes of 16 Cases With COVID19 and Mucormycosis: Experience From A Tertiary Care Center In India and Review of Literature

Abstract: Background-The sharp uptick in the cases of mucormycosis in the background of the COVID19 pandemic is a cause of concern and the reasons and it’s impact remains to be seen. We studied the clinical characteristics in patients with mucormycosis and COVID19 co-infection and performed a literature review.Methods-This retrospective study was conducted at tertiary centre in India. All patients admitted with COVID19 and mucormycosis were included, clinical details were obtained from hospital records. We did review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This patient also had homolateral facial palsy which is a feature of acute rhinocerebral mucormycosis. 5 Multiple cranial nerve involvement in mucormycosis infection has been reported by Paul S et al 10 In our study, two patients having mucormycosis infections developed facial palsy.…”
Section: Discussionsupporting
confidence: 68%
“…This patient also had homolateral facial palsy which is a feature of acute rhinocerebral mucormycosis. 5 Multiple cranial nerve involvement in mucormycosis infection has been reported by Paul S et al 10 In our study, two patients having mucormycosis infections developed facial palsy.…”
Section: Discussionsupporting
confidence: 68%
“…A multicentric retrospective study in India also showed a major risk factor in diabetes mellitus (75%) in COVID-19 and mucormycosis coinfection in comparison to chronic kidney disease (12.5%), chronic liver disease (6.25%), pulmonary tuberculosis (TB) (6.25%), and patients on immunosuppressive agents (6.25%). 70 Glucocorticoids are reported to cause immunosuppressive effects via transcriptional upregulation or repression of specific genes, especially nuclear factor κB (NF-κB). 71,72 It also affects T-lymphocyte interstitial pathology, which is itself a risk factor for invasive fungal infection in sinuses and lungs.…”
Section: Covid-19 and Pulmonary Mucormycosismentioning
confidence: 99%
“…Multiple reports from India have documented a precipitate rise in coronavirus disease 2019 (COVID-19)associated rhino-orbito-cerebral mucormycosis (CAROM) since March 2020. 1,2 The overall risk of developing CAROM in the backdrop of COVID-19 was recently estimated to be approximately 1 in 400. 2 CAROM in India is typically being noted 2 to 4 weeks from the onset of COVID-19.…”
mentioning
confidence: 99%
“…1,2 The overall risk of developing CAROM in the backdrop of COVID-19 was recently estimated to be approximately 1 in 400. 2 CAROM in India is typically being noted 2 to 4 weeks from the onset of COVID-19. The cause of the unexpectedly high incidence of CAROM in India has resulted in widespread speculation.…”
mentioning
confidence: 99%
See 1 more Smart Citation